Digital technologies as a tool of efficient logistics - Вербівська, Людмила Василівна (Revista de la Universidad del Zulia., 2023)
The study is dedicated to the justification of the need for the wide implementation of digital technologies in logistics activities, taking into account globalization challenges. The purpose of the article is to highlight the basics of implementing digital technologies as a tool ofefficientlogistics in modern conditions. The methodological basis of the study is a systematic approach, which allows studying logistics as a complex set of interdependent and interacting subsystems that have integral properties and develop under the influence of internal and external influencing factors. It has been proven that the use of information technologies in logistics makes it possible to: effectively solve current problems and eliminate possible problems in the future; improve the quality of logistics services; maximally load the capacity of logistics flows; rationalize material flows; increase the safety of transportation; optimize costs for the supply of resources and products; eliminate intermediate links by ensuring the transformation of information into forms that are convenient for consumers; increase the efficiency of information exchange and increase its security; implement new services and innovative customer support tools.
Keywords: Digital technologies, logistics, logistics sphere, logistics services, system approach